2018
DOI: 10.7567/1347-4065/aaecd7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the effect of indium composition on ultrafast carrier dynamics in InGaN alloys

Abstract: In this letter, we investigated the effect of indium composition on carrier relaxation mechanisms in InGaN alloys. Four high quality alloys with indium composition from 25% to 75% were fabricated using energetic neutral atomic-beam lithography/epitaxy molecular beam epitaxy. Using subpicosecond resolved photoluminescence at high carrier density, it was found the effective carrier lifetime extends with increasing indium composition. Moreover, the calculated initial carrier temperature also rises with higher ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…This folding is particularly important for acoustic modes as it brings these modes to the mini-Brillouin zone centre at appreciable energy (normally acoustic modes have close to zero energy at zone centre) and thus allows them to be optically active (Raman active) such that these folded acoustic modes can be directly emitted by hot carriers, thus providing an additional (if rather slow) route for carrier cooling to take place. 49 For SSPL, phonon folding simply limits the maximum temperature that carriers can reach in the steady state in NPLs, since they are always losing energy to LO phonons and to optical-like acoustic phonons in parallel, whereas QDs only have one channel for LO phonons and so attain a higher carrier temperature. However, for TRPL, the additional optical-like acoustic phonon channel does not make much difference until the temperature drops to a point at which very little energy is lost to LO phonons and acoustic phonon loss takes over and this is very slow, giving a long lifetime (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This folding is particularly important for acoustic modes as it brings these modes to the mini-Brillouin zone centre at appreciable energy (normally acoustic modes have close to zero energy at zone centre) and thus allows them to be optically active (Raman active) such that these folded acoustic modes can be directly emitted by hot carriers, thus providing an additional (if rather slow) route for carrier cooling to take place. 49 For SSPL, phonon folding simply limits the maximum temperature that carriers can reach in the steady state in NPLs, since they are always losing energy to LO phonons and to optical-like acoustic phonons in parallel, whereas QDs only have one channel for LO phonons and so attain a higher carrier temperature. However, for TRPL, the additional optical-like acoustic phonon channel does not make much difference until the temperature drops to a point at which very little energy is lost to LO phonons and acoustic phonon loss takes over and this is very slow, giving a long lifetime (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…This folding is particularly important for acoustic modes as it brings these modes to the mini-Brillouin zone centre at appreciable energy (normally acoustic modes have close to zero energy at zone centre) and thus allows them to be optically active (Raman active) such that these folded acoustic modes can be directly emitted by hot carriers, thus providing an additional (if rather slow) route for carrier cooling to take place. 49 …”
Section: Resultsmentioning
confidence: 99%
“…This has been observed in low-dimensional devices. [16][17][18][19][20][21][22] However, the mechanisms of PBE in these structures (i.e., quantum well [QW], quantum wire [QWR], and quantum dots [QDs]) are often coupled with other effects or mechanisms, making the PBE complex for analysis and control. Meanwhile, the most obvious reduction on carrier relaxation rate (or the longest hot carrier lifetimes) are typically observed in III-V material systems probably due to their excellent optoelectrical properties (e.g., their generally direct bandgap) and mature growth techniques (e.g., molecular beam epitaxy [MBE] and metal-organic chemical vapor deposition [MOCVD]), which give very high crystal quality.…”
Section: Introductionmentioning
confidence: 99%
“…A significant amount of research has indicated that phonon bottleneck effects (PBE, also referred to as “hot phonons”) are a key mechanism to realizing a significant reduction of carrier relaxation. This has been observed in low‐dimensional devices 16–22 . However, the mechanisms of PBE in these structures (i.e., quantum well [QW], quantum wire [QWR], and quantum dots [QDs]) are often coupled with other effects or mechanisms, making the PBE complex for analysis and control.…”
Section: Introductionmentioning
confidence: 99%
“…An HC‐SC consists of an absorber in which carriers are photogenerated, energy‐selective contacts (ESCs) that transmit carriers of specific energies, and electrodes. Carrier thermalization times exceeding 1 ns that are extremely longer than those in conventional SCs have been observed in semiconductor quantum structures, 7–9 nitrides, 9–11 and organic–inorganic hybrid perovskites 12 . An emerging technology is the use of intervalley scattering in semiconductors enhanced by internal electric field.…”
Section: Introductionmentioning
confidence: 99%